2014
DOI: 10.1007/s13402-014-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel saliva-based microRNA biomarker panel to detect head and neck cancers

Abstract: We show that we have developed a reliable method to isolate miRNAs from small volumes of saliva, and that the saliva-derived miRNAs miR-9, miR-134 and miR-191 may serve as novel biomarkers to reliably detect HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 40 publications
(39 reference statements)
2
94
0
1
Order By: Relevance
“…In addition, miR-191-5p is a potential target in treating radiation-resistant lung cancer according to the study by Liu and Huang (43). Several studies also reported that miR-191-5p may be of value as a prognostic and predictive biomarker in certain tumors, including breast cancer (44), osteosarcoma (45), and head and neck squamous cell carcinoma (46). Furthermore, miR-191-5p was suggested to be a potentially non-neoplastic biomarker to diagnose traumatic brain injury and predict the patient prognosis (47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-191-5p is a potential target in treating radiation-resistant lung cancer according to the study by Liu and Huang (43). Several studies also reported that miR-191-5p may be of value as a prognostic and predictive biomarker in certain tumors, including breast cancer (44), osteosarcoma (45), and head and neck squamous cell carcinoma (46). Furthermore, miR-191-5p was suggested to be a potentially non-neoplastic biomarker to diagnose traumatic brain injury and predict the patient prognosis (47).…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide and includes tumors of the pharynx, oral cavity and larynx [1][2][3][4]. Curcumin (diferuloylmethane), a principle ingredient in the spice turmeric, is well known for its anti-carcinogenic, antiinflammatory and pharmacological properties [5].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to metabolic diseases, 65 proteins are differentially expressed in the saliva of patients with type II diabetes mellitus [26]. There is potential for advancement in cancer salivary diagnostics as well; proteins, mRNA and miRNA have been shown to have distinct patterns in patients with breast cancer [27], head and neck squamous cell carcinoma [28], lung cancer [29], oral squamous cell carcinoma [30], and resectable pancreatic cancer [31] (Table 3). …”
Section: Salivary Diagnosticsmentioning
confidence: 99%